Moderating effect of money attitude on relationship between psychographic factors and status consumption among working women in the Klang Valley, Malaysia - Sandhu, Sukjeet Kaur (2018)
People crave for status. This status struggle waves for today’s consumer. The obsession with status seeking which displays through consumption of status good has emerged among working women who have experienced increased economic and social influence. While previous studies have presented different factors influences status consumption, a very critical element, which very few studies have included, is money attitude in their predictability model. The money attitude dimension has not been extensively researched especially among working women in Malaysia. The current study investigates the phenomenon of status consumption behaviour among Malaysian working women. Materialism, brand consciousness, social status display, attention to social comparison, collectivism and individualism were examining to predict the status consumption model. For the first time, money attitude was introduced as a moderator variable. Theories such as conspicuous consumption, social comparison and impression management theory were used to predict status consumption model. A sample of 410 working women from Klang Valley were selected through non probability sampling technique. Data for the research were collected through mall intercept concept. Four major mall in Klang Valley area were collected. The research predictability model was tested by using reliability analysis and descriptive analysis. Structural Equation Model (SEM) using Partial Least Square analysis was used to measure the level of status consumption and to investigate the moderating effect of money attitude. The results show that brand consciousness has the strongest relationship with status consumption followed by money attitude, materialism and individualism. The moderation effect of money attitude was also discussed. The results of the study reveals that money attitude as a moderator has a significant impact of the predictability model where R² improved from 60.0% to 66.2%. The role of money attitude is truly important variable in predicting the status consumption behavior. The study contributes to the body of knowledge by providing empirical evidence and improves the understanding of status consumption.